A randomized, double-blind phase I clinical trial of two recombinant dimeric RBD COVID-19 vaccine candidates: Safety, reactogenicity and immunogenicity - Pérez-Rodríguez, Sonia; de la Caridad Rodríguez-González, Meiby; Ochoa-Azze, Rolando; Climent-Ruiz, Yanet; Alberto González-Delgado, Carlos; Paredes-Moreno, Beatriz; Valenzuela-Silva, Carmen; Rodríguez-Noda, Laura; Perez-Nicado, Rocmira; González-Mugica, Raúl; Martínez-Pérez, Marisel; Sánchez-Ramírez, Belinda; et al. (Vaccine, 2022)
•Dimeric-RBD vaccines against SARS-CoV-2.•New adjuvant for COVID-19 vaccines.•Safety and immunogenicity of homologous and heterologous COVID-19 vaccination schedules.•Dimeric-RBD vaccines were safe and immunogenic, and induced live-virus neutralizing antibodies against SARS-CoV-2. The Receptor Binding Domain (RBD) of the SARS-CoV-2 spike protein is the target for many COVID-19 vaccines. Here we report results for phase I clinical trial of two COVID-19 vaccine candidates based on recombinant dimeric RBD (d-RBD). We performed a randomized, double-blind, phase I clinical trial in the National Centre of Toxicology in Havana. Sixty Cuban volunteers aged 19–59 years were randomized into three groups (20 subjects each): 1) FINLAY-FR-1 (50 µg d-RBD plus outer membrane vesicles from N. meningitidis); 2) FINLAY-FR-1A-50 (50 µg d-RBD, three doses); 3) FINLAY-FR-1A-25 (25 µg d-RDB, three doses). The FINLAY-FR-1 group was randomly divided to receive a third dose of the same vaccine candidate (homologous schedule) or FINLAY-FR-1A-50 (heterologous schedule). The primary outcomes were safety and reactogenicity. The secondary outcome was vaccine immunogenicity. Humoral response at baseline and following each vaccination was evaluated using live-virus neutralization test, anti-RBD IgG ELISA and in-vitro neutralization test of RBD:hACE2 interaction. Most adverse events were of mild intensity (63.5%), solicited (58.8%), and local (61.8%); 69.4% with causal association with vaccination. Serious adverse events were not found. The FINLAY-FR-1 group reported more subjects with adverse events than the other two groups. After the third dose, anti-RBD seroconversion was 100%, 94.4% and 90% for the FINLAY-FR-1, FINLAY-FR-1A-50 and FINLAY-FR-1A-25 respectively. The in-vitro inhibition of RBD:hACE2 interaction increased after the second dose in all formulations. The geometric mean neutralizing titres after the third dose rose significantly in the group vaccinated with FINLAY-FR-1 with respect to the other formulations and the COVID-19 Convalescent Serum Panel. No differences were found between FINLAY-FR-1 homologous or heterologous schedules. Vaccine candidates were safe and immunogenic, and induced live-virus neutralizing antibodies against SARS-CoV-2. The highest values were obtained when outer membrane vesicles were used as adjuvant. Trial registry: https://rpcec.sld.cu/en/trials/RPCEC00000338-En.